What Is This Thing Called Evaluation Theory? - Sebastian Lemire; Bianca Montrosse-Moorhead; Christina Christie (The Evaluation Center at Western Michigan University, 2024)
Background: Evaluation theory has and continues to play an important role in the practice and profession of evaluation. Over the years, and as the range of evaluation theories has continued to grow, evaluation scholars and practitioners have developed various visualized classification frameworks of evaluation theory, invoking images such as trees, rivers, the periodic table, metro maps, concept maps, and most recently gardens. Purpose: The purpose of this special issue is to explore different visualizations of evaluation theory and to discuss their benefits and implications for the practice and profession of evaluation. Setting: Not applicable. Intervention: Not applicable.  Research Design: Not applicable.  Data Collection and Analysis: Not applicable. Findings: Not applicable. Keywords: Evaluation theory, data visualization, research on evaluation, teaching evaluation